Burden of immune-related skin diseases worldwide, 1991–2021: insights and prediction from the Global Burden of Disease Study - Leng, Min; Qi, Ping; Li, Ronghua; Gong, Feiyu; Wei, Zairong (Frontiers in Immunology, 2025)
BackgroundImmune-mediated dermatological conditions, including dermatitis, urticaria, alopecia areata, and psoriasis, are common skin diseases that contribute to substantial health loss, economic burden, and pain across individuals of all ages worldwide.MethodsUsing data from the Global Burden of Disease (GBD) 2021 study, we analyzed age-standardized incidence, prevalence rate, and disability-adjusted life years (DALYs) for global main four immune-related skin diseases—including dermatitis (atopic, contact, and seborrheic), urticaria, alopecia areata, and psoriasis from 1991 to 2021, with corresponding 95% uncertainty intervals (UIs), stratified by sex, age, geographical location, and sociodemographic index (SDI). We further projected incidence through 2035 using a Holt-damped model incorporating trend components but excluding seasonality.​Results​Dermatitis had the highest estimated age-standardized prevalence rate (ASPR: 5459.07 per 100,000; 95% UI: 5064.87–5875.73), followed by psoriasis (354.07; 95% UI: 342.42–364.08), urticaria (1094.59; 95% UI: 969.18–1240.42), and alopecia areata (42.89; 95% UI: 41.74–44.14). Immune-related dermatoses consistently showed higher age-standardized rates in females than males. The estimated annual percentage change (EAPC) revealed distinct temporal patterns: dermatitis (-0.155) and alopecia areata (-0.127) showed slight declines, whereas psoriasis exhibited an upward trend (0.24), and urticaria remained stable with a modest increase (0.01). Age distribution: Dermatitis/urticaria peaked in children, alopecia areata in adulthood, and psoriasis in middle age.Conclusions​Immune-related skin diseases—including dermatitis, urticaria, alopecia areata, and psoriasis—are highly prevalent worldwide, with notable variations by age, sex, and region. Females are disproportionately affected. These trends underscore the need for targeted, sex- and region-specific public health interventions to optimize the allocation of healthcare.